Effects of early reading and writing intervention on Spanish school children - González- Valenzuela, María-Jose; Martín Ruiz, Isaías (Anales de Psicología / Annals of Psychology, 2023)
The aim of this paper is to analyse the reading and writing achievement of Spanish school children following an intervention conducted at an early age. The purpose of the intervention is to prioritise and systematise instruction in the alphabetic principles, phonological awareness, reading fluency, vocabulary, and text comprehension. The sample consists of 126 subjects, distributed between an instructed group (n=62) and an uninstructed group (n = 64). All the subjects were from average socio-cultural areas, with normal intelligence and with no physical, mental, and/or sensory deficits. Subjects were evaluated from the second year of Early Years Education (4 years of age) up to the first year of Primary Education (six years of age). The design was longitudinal with repeated measurements (four assessments), three intervention phases, two study variables (reading achievement and writing achievement), and two groups of subjects. Descriptive statistical analysis and repeated measures analyses of variance were performed. The results obtained indicate higher scores in reading and writing throughout all the assessments and significantly greater progress in the instructed group. These results demonstrate the effectiveness of early intervention in written language through systematic instruction in phonological awareness, the alphabetic principles, reading fluency, vocabulary, and text comprehension.